2019
DOI: 10.1161/circimaging.118.008513
|View full text |Cite
|
Sign up to set email alerts
|

Disease Activity in Mitral Annular Calcification

Abstract: Background: Mitral annular calcification (MAC) is associated with cardiovascular events and mitral valve dysfunction. However, the underlying pathophysiology remains incompletely understood. In this prospective longitudinal study, we used a multimodality approach including positron emission tomography, computed tomography, and echocardiography to investigate the pathophysiology of MAC and assess factors associated with disease activity and progression. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 25 publications
7
41
0
Order By: Relevance
“…Here, we have confirmed that increased 18 F-fluoride uptake provides an assessment of calcification activity within the coronary arteries, with uptake predicting progression in macroscopic calcium measured in individual plaques on CT (Figure 1 ), similar to previous results in the aortic valve and mitral valve annulus. 28 , 29 Indeed, while calcium scores remained static in lesions without uptake, there was progression of calcification in plaques with increased 18 F-fluoride uptake, with an ≈50% increase in median calcium score and calcium mass in as little as 12 months. Furthermore, the median change in calcium score in individual lesions with 18 F-fluoride uptake was almost 20× greater than the change in calcium score in those without uptake.…”
Section: Discussionmentioning
confidence: 98%
“…Here, we have confirmed that increased 18 F-fluoride uptake provides an assessment of calcification activity within the coronary arteries, with uptake predicting progression in macroscopic calcium measured in individual plaques on CT (Figure 1 ), similar to previous results in the aortic valve and mitral valve annulus. 28 , 29 Indeed, while calcium scores remained static in lesions without uptake, there was progression of calcification in plaques with increased 18 F-fluoride uptake, with an ≈50% increase in median calcium score and calcium mass in as little as 12 months. Furthermore, the median change in calcium score in individual lesions with 18 F-fluoride uptake was almost 20× greater than the change in calcium score in those without uptake.…”
Section: Discussionmentioning
confidence: 98%
“…BC image, A B without much effort to manually exclude the aneurysm part close to the bone. Although the BC technique was used in this study to effectively remove the spill in activity from the bone into the aneurysm, the application is not limited to aneurysm imaging, but in principle it can be applied to other mappable regions such as the aortic valves 19 and the mitral annulus 42 where an automated (or semiautomated) ROI can be drawn on the BC image without much effort to manually exclude the uptake from the hot region. Further study is, however, needed to validate this.…”
Section: Discussionmentioning
confidence: 99%
“…MAC progression appears to be more closely associated with the extent of baseline MAC and its inflammatory component, assessed by 18 F-fluorodeoxyglucose activity, than with eGFR. 47 The presence of MAC has been associated with mitral regurgitation, stenosis, or mixed valvular disease. In addition, MAC is associated with greater cardiovascular risk, and higher risk for endocarditis, and atrial arrhythmias.…”
Section: Clinical Assessmentmentioning
confidence: 99%